MMS Observations of the Multiscale Wave Structures and Parallel Electron Heating in the Vicinity of the Southern Exterior Cusp. Issue 3 (26th March 2021) - Nykyri, K.; Ma, X.; Burkholder, B.; Rice, R.; Johnson, J. R.; Kim, E‐K.; Delamere, P.; Michael, A.; Sorathia, K.; Lin, D.; Merkin, S.; Fuselier, S.; et al.
Abstract: Understanding the physical mechanisms responsible for the cross‐scale energy transport and plasma heating from solar wind into the Earth's magnetosphere is of fundamental importance for magnetospheric physics and for understanding these processes in other places in the universe with comparable plasma parameter ranges. This paper presents observations from the Magnetosphere Multiscale (MMS) mission at the dawn‐side high‐latitude dayside boundary layer on February 25, 2016 between 18:55 and 20:05 UT. During this interval, MMS encountered both the inner and outer boundary layers with quasiperiodic low frequency fluctuations in all plasma and field parameters. The frequency analysis and growth rate calculations are consistent with the Kelvin‐Helmholtz instability (KHI). The intervals within the low frequency wave structures contained several counter‐streaming, low‐ (0–200 eV) and mid‐energy (200 eV–2 keV) electrons in the loss cone and trapped energetic (70–600 keV) electrons in alternate intervals. The counter‐streaming electron intervals were associated with large‐magnitude field‐aligned Poynting fluxes. Burst mode data at the large Alfvén velocity gradient revealed a strong correlation between counter streaming electrons, enhanced parallel electron temperatures, strong anti‐field aligned wave Poynting fluxes, and wave activity from sub‐proton cyclotron frequencies extending to electron cyclotron frequency. Waves were identified as Kinetic Alfvén waves but their contribution to parallel electron heating was not sufficient to explain the >100 eV electrons. Plain Language Summary: Electrons, The Riders of the Space Hurricane: Earth's magnetic field forms a barrier in the solar wind, called the magnetosphere, which provides some shielding against solar radiation and galactic cosmic rays. However, this shield can be penetrated by process called magnetic reconnection, and secondary processes created by giant "fluid‐scale" space hurricanes (typically 20, 000–36, 000 km in wave length) aka Kelvin‐Helmholtz (KH) waves that are whipped along the magnetic barrier by solar wind flow. One of the puzzling problems of the Earth's magnetosphere is that it is so hot: both electrons and ions are heated to tens of millions of degrees when they get transported from solar wind through the Earth's magnetic barrier. This article shows observations of multiscale wave structures, spanning the fluid‐scales, ion scales and electron scales detected by the NASA's magnetosphere multiscale mission consisting of four satellites. We show how these large‐scale waves contain ion and electron scale waves that are able to produce some of the observed electron heating and acceleration. We "fingerprint" the exact plasma wave modes (tornadoes) inside the space hurricane that are responsible for resonantly whipping and transferring the wave energy to the electrons surfing the wave. Key Points: Magnetosphere multiscale observed periodic low frequency waves, likely Kelvin‐Helmholtz instability, at the dawn‐flank high‐latitude boundary layer Higher frequency waves within the low frequency waves were associated with enhanced Poynting flux and parallel electron heating Waves close to proton cyclotron frequency were identified as Kinetic Alfvén waves, and were evaluated to provide partial heating